Sustainable marketing strategies: Creating business value by meeting consumer expectation - Krunal Trivedi; Pooja Trivedi; Vandana Goswami (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
Sustainable Marketing strategies are unavoidable for 21st century businesses. Companies have started investing huge amount on these activities. Consumers do expect companies to adopt sustainable strategies but realizing one's need is the only drive for any consumer. Thus, there is gap between business sustainability practices and consumers' expectations. To address this gap, the paper proposes a conceptual framework for sustainability strategies that businesses must adopt. The proposed framework can be an important standpoint for businesses to meet consumers' expectations without compromising business value. The paper identified four major sustainable marketing strategies to be integrated into business practices.
Keywords: M19; M31; 650; Sustainable marketing strategies; business value; consumer expectations; societal marketing; modern marketing